Analysis of Water Quality Status in Tuntang River, Semarang Regency in 2022 - Andri Saputra; Arum Siwiendrayanti (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2023)
Tuntang River is a river located in Tuntang District, Semarang Regency. The study was conducted to determine the quality of river water, status of river water quality and sources of river pollution in the Tuntang River in the Upstream Segment so that steps can be taken to tackle pollution in the Tuntang River in the Upstream Segment. This research was conducted during the dry season, samples were taken during the January-June 2022 period. The quality status was assessed using the Pollution Index (PI) method. The results of the study of 2 sample points were at lightly polluted status based on Class II Quality Standards according to Government Regulation Number 22 of 2021. Based on calculations using the PI method at Point 1 were in normal conditions. Meanwhile, point 2 is in a moderately polluted condition. In the analysis using Geography Information System (GIS) there are several sources of pollution, namely, in the domestic sector, plantation sector, agricultural sector (rice fields and fields), livestock sector, and mining sector.